Belt and Road Initiative and Nepal’s Economic Perspective: Regionality and Specificity - Adhikari, Ashish (Kathmandu School of Law Review, 2018)
The collective participation in Belt and Road Initiative expects to forego unequal integration and to start inclusive and fair development. Nepal also participates in this initiative with similar aspirations. China has linked her West Development Strategy with BRI. Nepal’s connectivity is now through Western the autonomous region of Tibet, which comes in the form of bilateral cooperation. What kind of participation in Belt and Road Initiative will give best economic benefits to Nepal? As an answer to this question, this paper proposes and argues for two distinct features: Regionality and Specificity. Regionality refers to priority concentration on the directly connected Tibet and associated role of adjoining provinces like Sichuan, Yunnan and Xinjiang. Specificity refers to the study of specific sectors like agriculture, industry, finance, tourism of these regions. The study of comparative requirement of these regions (regionality) in specific sectors (specificity) is paramount to get benefits from BRI.